Soil carbon: A silver bullet for climate change mitigation? Finding a middle way - Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Increasing the storage of carbon in the soil has been a controversial strategy for addressing climate change mitigation. What is the potential and why is there debate about this? How can we push beyond the debate to constructive action?